PEMANFAATAN MEDIA DOMBA DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA DINI - Norhikmah; Hairun Nisa; Desy Maimunah; Nor Latifah; Aghnaita; Sri Hidayati; Ali Iskandar Zulkarnain (Kreasi: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service is to use sheep media in developing early childhood creativity. The method used is service-learning. The targets in this service are educators at TKIT Asy Syaamil Qur'anic Fullday School. The results of the service show that educators at TKIT Asy Syaamil Qur'anic Fullday School can make sheep media well. This media can then be used to develop early childhood creativity and be used in the learning process and introduction of animal themes for students.